Expression of distinct α(1)-adrenoceptor phenotypes in the iris of pigmented and albino rabbits - Muramatsu, I (Blackwell Publishing Ltd, 2009)
BACKGROUND AND PURPOSE: The expression of multiple pharmacological phenotypes including α(1L)-adrenoceptor has recently been reported for α(1)-adrenoceptors. The purpose of the present study was to identify α(1)-adrenoceptor phenotypes in the irises of pigmented and albino rabbits. EXPERIMENTAL APPROACH: Radioligand binding and functional bioassay experiments were performed in segments or strips of iris of pigmented and albino rabbits, and their pharmacological profiles were compared. KEY RESULTS: [(3)H]-silodosin at subnanomolar concentrations bound to intact segments of iris of pigmented and albino rabbits at similar densities (approximately 240 fmol·mg(−1) protein). The binding sites in the iris of a pigmented rabbit were composed of a single component showing extremely low affinities for prazosin, hydrochloride [N-[2-(2-cyclopropylmethoxyphenoxy)ethyl]-5-chloro-α,α-dimethyl-1H-indole-3-ethamine hydrochloride (RS-17053)] and 5-methylurapidil, while two components with high and low affinities for prazosin, RS-17053 and 5-methylurapidil were identified in irises from albino rabbits. In contrast, specific binding sites for [(3)H]-prazosin were not clearly detected because a high proportion of non-specific binding and/or low affinity for prazosin occurred. Contractile responses of iris dilator muscle to noradrenaline were antagonized by the above ligands, and their antagonist affinities were consistent with the binding estimates at low-affinity sites identified in both strains of rabbits. CONCLUSIONS AND IMPLICATIONS: A typical α(1L) phenotype with extremely low affinity for prazosin is exclusively expressed in the iris of pigmented rabbits, while two distinct phenotypes (α(1A) and α(1L)) with high and moderate affinities for prazosin are co-expressed in the iris of albino rabbits. This suggests that a significant difference in the expression of phenotypes of the α(1)-adrenoceptor occurs in the irises between the two strains of rabbits.